Parametric Analysis of Disperse Phase Soot Transport and Mass Capture in an Ionized Diesel Exhaust Crossflow - Bangbang Kurniawan; Asep; Agung Sudrajat; Dhimas Satria; Dwinanto Sukamto; Sunardi; Syarif Abdullah; Mekro Permana Pinem (Fakultas Teknik Universitas Pancasila, 2026)
This study investigates the influence of applied voltage, electrode spacing, and operating duration on the collection rate of fine particulate matter (PM2.5) in a diesel engine Electrostatic Precipitator (ESP). Using a laboratory-scale ESP integrated with a diesel exhaust system, experiments were conducted at three voltage levels (1.5, 4.5, and 6.7 kV), three electrode spacings (1.5, 2.0, and 2.5 cm), and three operating durations (3, 5, and 7 min). Precipitator performance was quantified using the gravimetric method. The peak particulate collection rate reached 1.10 mg/s under optimized operating parameters (6.7 kV applied voltage, 1.5 cm electrode spacing, and a 7 min operational duration. Statistical analysis via Analysis of Variance (ANOVA) indicates that operating time is the most dominant factor governing the recorded particulate collection rate. While increasing the applied voltage and minimizing electrode spacing demonstrated clear positive physical trends in collection performance by boosting local electric field intensity, their standalone individual effects were not statistically significant at a 95% confidence level. This behaviour reveals the kinetic nature of gravimetric mass accumulation, where sufficient residence time is required to differentiate field-driven transport variances from baseline analytical thresholds. These findings provide critical baseline insights for optimizing compact, low-pressure-drop electrohydrodynamic emission controls on small-scale diesel power systems.